Analysis of Students’ Difficulties in Completing Final Projects - Mudmainna, Mudmainna (Newinera Publisher, 2025)
The process of completing an undergraduate thesis remains a significant challenge for students, particularly in translating research data into a coherent scientific paper. Difficulties often arise in managing data obtained from questionnaires, interviews, and documentation, leading to uncertainty about the initial and subsequent steps in academic writing. This study aims to explore the challenges students face in thesis writing and the role of academic supervisors in supporting the process. Employing a descriptive qualitative approach, the research was conducted at the Institute of Teacher Training and Technology (Institut Keguruan dan Teknologi) Larantuka, East Flores Regency, involving eighth-semester students and academic supervisors selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings indicate that students’ difficulties are influenced by internal factors including challenges in topic selection, limited references, time management, lack of research experience, and psychological barriers and external factors, such as inadequate supervision, unsupportive environments, and insufficient faculty-level management. The study concludes that thesis completion is shaped by both individual capabilities and external support systems. Strengthening academic writing practices, improving supervision strategies, and providing institutional support through workshops and structured guidance are crucial for facilitating effective and timely thesis completion. The implications of this study emphasize the importance of collaborative efforts among students, supervisors, and higher education institutions to enhance the quality and efficiency of undergraduate thesis writing.